Acriflavine-Functionalized Silica@Manganese Ferrite Nanostructures for Synergistic Radiation and Hypoxia Therapies - Eckenberger, Elisabeth; Raczka, Theodor; Neuhuber, Winfried; Distel, Luitpold; Klein, Stefanie (ACS Applied Bio Materials, 2023)
Mesoporous and nonmesoporous SiO2@MnFe2O4 nanostructures were loaded with the hypoxia-inducible factor-1 inhibitor acriflavine for combined radiation and hypoxia therapies. The X-ray irradiation of the drug-loaded nanostructures not only triggered the release of the acriflavine inside the cells but also initiated an energy transfer from the nanostructures to surface-adsorbed oxygen to generate singlet oxygen. While the drug-loaded mesoporous nanostructures showed an initial drug release before the irradiation, the drug was primarily released upon X-ray radiation in the case of the nonmesoporous nanostructures. However, the drug loading capacity was less efficient for the nonmesoporous nanostructures. Both drug-loaded nanostructures proved to be very efficient in irradiated MCF-7 multicellular tumor spheroids. The damage of these nanostructures toward the nontumorigenic MCF-10A multicellular spheroids was very limited because of the small number of nanostructures that entered the MCF-10A spheroids, while similar concentrations of acriflavine without nanostructures were toxic for the MCF-10A spheroids.
CRIS-Team Scopus Importer:2023-09-29
Keywords: drug delivery; hypoxia; magnetic mesoporous silica@MnFe2O4 nanoparticles; magnetic silica@MnFe2O4 nanoparticle acriflavine; multicellular tumor spheroids; radiation therapy

Customizable Induction Heating Profiles: from Tailored Colloidally Stable Nanoparticles Toward Multi-Stage Heatable Supraparticles - Luthardt, Leoni; Raczka, Theodor; Hurle, Katrin; Müssig, Stephan; Mandel, Karl (Advanced Functional Materials, 2024)

Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene† - Schörner, Markus; Solymosi, Thomas Andrew; Raczka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt–alumina on steel beads, b) Pt–alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with P
Keywords: Hydrogen storage; Inductive heating; LOHC; Platinum; Perhydro benzyltoluene

Influence of magnetic interactions in iron oxide nanoparticle polymer composites on magnetism and induction heating - Raczka, Theodor; Wolf, Andreas; Reichstein, Jakob; Stauch, Claudia; Schug, Benedikt; Müssig, Stephan; Mandel, Karl (Journal of Magnetism and Magnetic Materials, 2024)
Induction heating of composite materials is of great interest in fields such as controlled polymer curing or degradation, self-healing or contactless joining. Ferrimagnetic iron oxide nanoparticle (IONPs) are suitable candidates for a powder additive to provide this inductive heating functionality, while being low-cost, abundant and a well-studied material class. Varying IONP size, morphology or doping facilitates fine-tuning of their heating properties. However, the interactions of such IONP additives in material composites are often neglected and can significantly alter the induction heating mechanism. In this work, we systematically vary the IONP interactions in polydimethylsiloxane composite materials by integrating 1.) dispersed IONPs 2.) supraparticles of IONPs (micrometer-assemblies), and 3.) oven-dried hard agglomerated IONPs. Additionally, these three levels of interaction are investigated for three different IONPs types (dodecahedrally and octahedrally shaped, as well as cobalt-doped). In general, dispersed IONPs reveal a broader hysteresis and therefore a faster heating curve. We highlight that not only IONP characteristics (size, morphology, doping), but also excitation field strength and foremost IONP interactions in the composite materials are parameters that are interdependent regarding induction heating and need to be considered as such for optimization in an application-oriented scenario.<br
Created from Fastlane, Scopus look-up
Keywords: Iron oxide nanoparticles; Induction heating; Magnetic interactions; Nanoparticle morphology; Micro-assemblies; Coercive field strength

Multifunctional Polymer Composites for Automatable Induction Heating with Subsequent Temperature Verification - Reichstein, Jakob; Raczka, Theodor; Stauch, Claudia; Schug, Benedikt; Müssig, Stephan; Mandel, Karl (Advanced Engineering Materials, 2024)
Manipulating ferromagnetic particles using an alternating current (AC) magnetic field is a versatile method for quick, local, and on-demand heat generation. These particles can be incorporated into various matrices as heating elements. Their heat release can be controlled by adjusting process or material parameters. Herein, a proof-of-concept for a flexible polymer composite with customizable magnetically triggered heat release due to prior object identification via fluorescence readout is presented. The maximum temperature resulting from this process can be determined through a second fluorescence readout ex post. This novel combination of functionalities results from the synergistic interaction of inductively heatable magnetic supraparticles (SPs) and luminescent communicating SPs in one polydimethylsiloxane composite. The surface of the composite can be heated to the maximum temperatures of choice in a range between 125 and 200 °C within 2 s. Heat release and temperature verification provide spatial resolution of millimeters. The identification signature and the working range of the temperature indication functionality of the composite are customizable by exploiting its modular material design. The temperature indication functionality of the composite offers spatial resolution and ex-post readout at any point of interest, making it a versatile alternative to established optical thermometry methods.<br
Keywords: supraparticles; magnetic nanoparticle; induction heating; temperature indicators; smart additives

Supraparticles on beads for supported catalytically active liquid metal solutions - the SCALMS suprabead concept - Zimmermann, Thomas; Madubuko, Nnamdi; Groppe, Philipp; Raczka, Theodor; Dünninger, Nils; Taccardi, Nicola; Carl, Simon; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Wasserscheid, Peter; Mandel, Karl; Haumann, Marco; et al. (Materials Horizons, 2023)
A novel GaPt-based supported catalytically active liquid metal solution (SCALMS) material is developed by exploiting the suprabead concept: Supraparticles, i.e. micrometer-sized particles composed of nanoparticles assembled by spray-drying, are bonded to millimeter-sized beads. The suprabeads combine macroscale size with catalytic properties of nanoscale GaPt particles entrapped in their silica framework.
Created from Fastlane, Scopus look-up

Thermite Reactions within Liquid Gallium/Iron Oxide Supraparticles Triggered Via Induction Heating - Raczka, Theodor; Groppe, Philipp; Hurle, Katrin; Moritz, Michael; Papp, Christian; Mandel, Karl; Wintzheimer, Susanne (ACS Applied Nano Materials, 2025)
Thermite reactions are well-known for mixtures of aluminum and iron oxide. However, other reactive metals, such as gallium, were not studied in this application, and the use of induction as an external trigger for the thermite reaction has not been established. In this work, supraparticles of gallium and iron oxide nanoparticles were synthesized to combine a low melting point with inductive heating properties. The enabled thermite-like redox reactions generate temperatures up to 900 °C within seconds in an alternating magnetic field, tunable by the material’s gallium content. Induction heating profiles are thus significantly expanded and could be applied for targeted heat-on-demand.
CRIS-Team Scopus Importer:2025-05-23
Keywords: gallium nanoparticles; induction heating; iron oxide nanoparticles; spray-drying; supraparticles; thermite